Cryoablation for advanced non-small cell lung cancer: a protocol for a systematic review - Dan Wang; Yu Chen; Hua Duan; Shu-Yue Zheng; Chufan Luo; Xueni Fang; Haoyue Pang; Man Wang; Tian Zhou; Quanwang Li; Kaiwen Hu (BMJ Open)
Introduction National Comprehensive Cancer Network has recommended cryoablation to replace the resection in the treatment of medically operable non-small cell lung cancer (NSCLC). Cryoablation also has been used for the advanced NSCLC in randomised controlled trials. However, they have not been systematically reviewed. Here, we provide a protocol to evaluate the effectiveness and safety of cryoablation in the treatment of advanced NSCLC.Methods and analyses We will search PubMed, Embase, the Cochrane Library, Chinese Biomedical Database, China National Knowledge Infrastructure, Wanfang Database and Chinese Scientific Journal Database without language restrictions from inception until 1 February 2020. Trial registers (International Clinical Trials Registry platform, the US National Institutes of Health Ongoing Trials Register and the ISRCTN registry) and reference lists of retrieved articles will also be searched. Two reviewers will independently extract data on participants, interventions, comparisons, outcomes and assess the methodological quality by the Cochrane risk of bias tool. The strength of evidences will be evaluated according to the Grading of Recommendations Assessment, Development and Evaluation approach. Review Manager V.5.3 software will be used for data analyses. Meta-analyses will be performed if the data are sufficiently homogeneous. The primary outcomes will be objective response rate and overall survival. The secondary outcomes will be adverse effects, health-related quality of life, changes of immune indicators and surrogate outcomes (disease control rate, progression-free survival and survival rate).Ethics and dissemination Ethics approval is not required, as this study will not involve patients. The results of this study will be submitted to a peer-reviewed journal for publication, to inform both clinical practice and further research.PROSPERO registration number CRD42019138660.